5-[(Benzo[d][1,3]dioxol-5-yl)methyl]-3-[4-(pyridin-2-yl)phenyl]-4,5-dihydroisoxazole - Nasseem El-Khatatneh; A. C. Vinayaka; Chandra; M. P. Sadashiva; S. Jeyaseelan; M. Mahendra (IUCrData, 2017)
In the molecule of the title compound C22H18N2O3, the benzodioxole and dihydroisoxazole rings are bridged via a methylene (CH2) group. The linkage is disordered over two positions with a occupancy factors of 0.887 (5) and 0.113 (5). The dihydroisoxazole and pyridine rings exhibit syn-clinal and anti-periplanar conformations with respect to the benzodioxole and benzene ring groups, as quantified by the torsion angle values of 70.7 (3) and 157.00 (17)°. Aside from van der Waals contacts, there are no significant intermolecular interactions.